Abnormal psychology - Nolen-Hoeksema, Susan (Mc-Graw Hill, 2007)
Abnormal psychology, by award-winning teacher and noted researcher Susan Nolen-Hoeksema, this text blends cutting-edge research in psychopathology with compassion for people who suffer from psychological disorders. Capturing the excitement of major advances in biological and psychosocial research and treatment alternatives, Abnormal Psychology imparts a true enthusiasm for and appreciation of scientific investigation. The authors scientific and caring approach, combined with strong study tools, has won accolades from instructors and students alike. The fourth edition reflects greater emphasis on integrated approaches to abnormal psychology, a constant drive to make biological information clear to students, and a stronger focus on empirical research and diversity.